G379(P) Twin to Twin Transfusion syndrome – The Lost Kidney. (7th April 2014) - Raychaudhuri, R; Yadav, P; Shroff, R; Ledermann, S
Abstract : Aim: To describe a cohort of children who presented to a tertiary renal service with a history of twin to transfusion syndrome (TTTS). To describe the age, mode of presentation, renal functions at presentation and long term outcome. Methods: Retrospective case note review from 2000–2013 of all children with a history of TTTS presenting to a tertiary centre for specialist renal input. The diagnosis of TTTS was based on antenatal ultrasonographic evidence of TTTS or on the (weight/haemoglobin discrepancy). Results: Eight sets of twins were identified. GA ranged from 29+2–34+2 weeks. All were monochorionic twins. Four twins had intrauterine laser treatment for TTTS. Age at presentation ranged from 1 day to 10 yrs 7 months. In our cohort 6 were donor twins and 2 were recipient twins. Six children were referred from neonatal units with renal impairment. Serum creatinine ranged from 126–400 micromol/L at presentation. Ultrasound of at presentation showed small, echogenic kidneys, some with cystic dysplastic changes. All the 8 children have chronic kidney disease (CKD) stage 3–5. Four children were transplanted and the rest continue to receive standard CKD management. Four had neurological deficits at follow up, ranging from mid developmental delay to severe global developmental delay with hypsarrythmia and difficult to control seizures and visual impairment. Two twin pairs had lost their siblings in utero. The remaining six twin siblings were alive and well at last follow up. Conclusion: TTTS is caused by an unbalanced shunting of blood between monochorionic twins. Chronic hypotension and hypovolaemia causes renal insufficiency in the donor twin. However two twins in our cohort were recipients. Previous studies have reported no long term renal impairment after intrauterine laser treatment of severe TTTS. This case series highlights the renal complications associated with TTTS. Despite the known risk of CRF in TTTS following intervention, our series also included two late/incidental presentations. This highlights the need to be aware of this complication in TTTS survivors and consider appropriate screening during follow up.